High Prevalence of Staphylococcus aureus Enterotoxin Gene Cluster Superantigens in Cystic Fibrosis Clinical Isolates - Fischer, Anthony J. (Genes (Basel), 2019)
Background: Staphylococcus aureus is a highly prevalent respiratory pathogen in cystic fibrosis (CF). It is unclear how this organism establishes chronic infections in CF airways. We hypothesized that S. aureus isolates from patients with CF would share common virulence properties that enable chronic infection. Methods: 77 S. aureus isolates were obtained from 45 de-identified patients with CF at the University of Iowa. We assessed isolates phenotypically and used genotyping assays to determine the presence or absence of 18 superantigens (SAgs). Results: We observed phenotypic diversity among S. aureus isolates from patients with CF. Genotypic analysis for SAgs revealed 79.8% of CF clinical isolates carried all six members of the enterotoxin gene cluster (EGC). MRSA and MSSA isolates had similar prevalence of SAgs. We additionally observed that EGC SAgs were prevalent in S. aureus isolated from two geographically distinct CF centers. Conclusions: S. aureus SAgs belonging to the EGC are highly prevalent in CF clinical isolates. The greater prevalence in these SAgs in CF airway specimens compared to skin isolates suggests that these toxins confer selective advantage in the CF airway.